MEMBANGUN KESADARAN KEWARGANEGARAAN DAN KEBERLANJUTAN PADA MAHASISWA PENDIDIKAN ANTROPOLOGI KELAS B STAMBUK 2021 UNIVERSITAS NEGERI MEDAN - Kristina Pujasari Sitompul; Febrianti Hutagalung; Theresia Saragih; Fandy Tarigan; Sri Yunita (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
Civic education plays an important role in shaping a critical, responsible, and aware young generation of citizens. Through this education, students are expected to be able to understand national values, pluralism, tolerance, and actively participate in social and political life, both on and off campus. Challenges such as discrimination, extremism, and social indifference still pose a threat to the spirit of citizenship among students. Therefore, civic education aims to raise awareness of the importance of national defense, democracy, and diversity. In addition, this education also emphasizes the importance of sustainability, where the younger generation is encouraged to play a role in preserving the environment and participating in policies that support social welfare. This article uses a qualitative approach to examine civic awareness among students, as well as how civic education can strengthen the character of the younger generation as responsible citizens who care about social and political challenges in the digital era.